ANALISIS EFISIENSI PEMASARAN UBI KAYU DI PROVINSI LAMPUNG - Anggraini, Nuni; Hasyim, Ali Ibrahim; Situmorang, Suriaty (Jurnal Ilmu-Ilmu Agribisnis, 2013)
This research aims to analyze the efficiency of cassava marketing system in Lampung Province. Theresearch was conducted purposively in Lampung Tengah and Lampung Utara in May-June 2012. Farmerrespondents were chosen randomly and marketing channel respondents were taken by tracing marketingnetworks. Data consisted of primary and secondary data. Data analysis included analysis of marketingsystem efficiency. The results showed that the marketing system of cassava in Lampung Province wasefficient with producer share (Ps) of more than 80 %, with the following conditions: (a) the market structurewas almost a perfect competition. (b) the market conduct: cassava farmers had no difficulty in marketingtheir product. (c) the market performance: there were two marketing channel; marketing margin and ProfitMargin Ratio were relatively small, and the elasticity of price transmission was less than one.